enter image description here

Hi guys, I've calculated the first part, but I don't understand how it is related with triangle inequality. Can someone help?Thanks!

  • In this context, the triangle inequality says that the modulus of the first integral is less than or equal to the second integral. – Greg Martin Sep 18 '16 at 7:56
up vote 1 down vote accepted

First, parametrize the $\{|z| = 1\}$ by $z = e^{i\theta}$. Then the first integral becomes \begin{align} \int_{|z|=1} (z-1)\ dz = \int^{2\pi}_0 (e^{i\theta}-1)ie^{i\theta}\ d\theta = 0. \end{align} For the second integral, we have \begin{align} \int_{|z|=1} |z-1||dz| = \int^{2\pi}_0 |e^{i\theta}-1| dt = \int^{2\pi}_0 |\cos\theta-1 + i\sin\theta|\ dt = \int^{2\pi}_0 \sqrt{(1-\cos\theta)^2+\sin^2\theta}\ d\theta = \int^{2\pi}_0\sqrt{2-2\cos\theta}\ d\theta = 2\int^{2\pi}_0 |\sin(\theta/2)|\ d\theta = 8. \end{align} Indeed, we have the triangle inequality \begin{align} \left|\int_{|z|=1}(z-1)\ dz\right| \leq \int_{|z|=1} |z-1||dz|. \end{align}

Your Answer

By clicking "Post Your Answer", you acknowledge that you have read our updated terms of service, privacy policy and cookie policy, and that your continued use of the website is subject to these policies.

Not the answer you're looking for? Browse other questions tagged or ask your own question.